Ethnoculture in literary translation: a linguocognitive and pragmatic analysis of uzbek-english representation - Musabekova, Madina Narimanbekovna (The Lingua Spectrum, 2026)
The article provides a comprehensive analysis of ethnoculture as a system-forming component of literary text and a key factor in Uzbek-English translation. Ethnoculture is examined from linguocognitive and pragmatic perspectives as a set of culturally marked concepts and realia shaping the national worldview. Based on Uzbek literary prose, the study identifies typological groups of ethnocultural units and analyzes their representation in English translation. Particular attention is paid to equivalence, semantic transformation, and preservation of cultural code.